Analisis Kemampuan Komunikasi Matematis Siswa dalam Menyelesaikan Permasalahan Kontekstual Berdasarkan Gender Kelas VIII-G SMPN 23 Semarang - Dewi Rachmawati; Ahmad Aunur Rohman; Yolanda Norasia (UIN Walisongo Semarang, 2025)
Mathematical communication skills are the basic ability to formulate initial concepts in solving mathematical problems. The level of mathematical communication skills can be influenced by various factors, one of which is gender. This study used a qualitative method through a descriptive approach, with the aim of describing the mathematical communication skills of class VIII-G students at SMPN 23 Semarang based on gender. Data were obtained through tests, questionnaires, and interviews. The results showed that students in the masculine, feminine, and androgynous categories mastered mathematical communication skills. Students with masculine and androgynous genders had the same understanding of all mathematical communication skill indicators used, while students with feminine genders failed to master any of the mathematical communication skill indicators used. The difference in mastery of mathematical communication skill indicators between masculine and androgynous students and feminine students lies in forming mathematical models through pictorial illustrations.